Stargirl. The complete second season. [videorecording (DVD)] - Bassinger, Brec, 1999-; Monreal, Yvette, 1992-; Washington, Anjelika; Gellman, Cameron (Warner Bros., 2022)
It follows high school sophomore Courtney Whitmore and her stepfather Pat Dugan as she leads an unlikely group of young heroes to take on the legacy of DC's very first superhero team, the Justice Society of America. In the thrilling second season, Courtney and her friends take on one of the most frightening adversaries in DC's mythology the dark entity of corruption known as Eclipso.